Hirami lemon ( var. ) modulates the gut-brain axis in a chronic mild stress-induced depression mouse model - Tsai, Po-Heng; Wu, Pei-Chen; Li, Hui-Ru; Senthil Kumar, K. J; Wang, Sheng-Yang (Food & function, 2023)
Citrus reticulata var. depressa , commonly known as Hirami lemon, is a native citrus species found in Taiwan and Okinawa islands of Japan. While several Citrus species are known to possess antidepressant activity by modulating the gut microbiota, the antidepressant effect of Hirami lemon and its underlying mechanisms have not been thoroughly investigated. In this study, we explored the potential antidepressant efficacy of the fruit extract (CD) and the essential oil (CDE) from Hirami lemon peel using a chronic mild stress (CMS)-induced mouse model and analyzed the association of gut microbiome changes. Our findings revealed that mice subjected to CMS exhibited anxiety- and depression-like behaviors as assessed by elevated plus-maze and forced swimming tests, respectively. Significantly, oral administration of CDE and CD notably reversed CMS-induced depression- and anxiety-like behaviors in CMS-induced mice. Moreover, compared to the non-stressed group, CMS significantly altered the gut microbiome, characterized by highly diverse bacterial communities, reduced Bacteroidetes, and increased Firmicutes. However, oral administration of CDE and CD restored gut microbiota dysbiosis. We also performed a qualitative analysis of CD and CDE using UPLC-MS and GC-MS, respectively. The CD contained 25 compounds, of which 3 were polymethoxy flavones and flavanones. Three major compounds, nobiletin, tangeretin and hesperidin, accounted for 56.88% of the total relative peak area. In contrast, the CDE contained 11 terpenoids, of which 8 were identified as major compounds, with d -limonene (45.71%) being the most abundant, followed by γ-terpinene (34.65%), linalool (6.46%), p -cymene (2.57%), α-terpineol (2.04%), α-pinene (1.89%), α-terpinolene (1.46%), and β-pinene (1.16%), accounting for 95.94% of the total oil. In conclusion, our study demonstrated the potential of Hirami lemon as a source of natural antidepressant agents for the prevention and treatment of major depressive disorders. Hirami lemon modulates the gut-brain axis in a chronic mild stress-induced depression mouse model.